INVESTIGATE THE SUPPORTIVE ROLE OF MANAGEMENT AND THE INDEPENDENCE OF THE INTERNAL AUDITOR IN THE EFFECTIVENESS OF INTERNAL AUDIT - Mehmet Hanifi AYBOGA, Farshad Ganji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In today's world, increasing the quantity and quality of independent auditing is generally possible by relying more on internal controls. Auditors' assessment of the internal controls of business units is how effective audit programs are set up. Accordingly, in this study, two intra-organizational factors including management support for internal audit and internal audit independence were examined and thus the effect of the above two factors (as an independent variable) on the effectiveness of internal audit (dependent variable) Was tested. The statistical sample is estimated at 200 managers and auditors according to Krejcie and Morgan table. According to the statistical population, the whole population has been selected as a sample and 170 usable questionnaires were obtained from which we examined the results of the study. The results of the present study show that the variables of internal audit independence, management support for internal audit have a significant relationship with the effectiveness of internal audit.